Effectiveness of Maja Leaf (Aegle Marmelos) Extract to The Process of Infertilization - Ima Rahmawati; Emyk Windartik; Eka Nur Soemah; Ifa Roifah (Universitas Padjadjaran, 2019)
Modern contraceptives were widely used derived from steroids and potentially invite side effects such as weightgain, menstrual cycle disorders, nausea and elevated blood pressure. Currently, the community began to switchtraditional herbs are relatively safer. Maja Leaf (Aegle Marmelos) contain many fitosteroles (β-sitosterol andstigmasterol) one of its functions is hormonal contraception by inhibiting the process of ovulation. This researchaims to know the effect of Maja Leaf (Aegle Marmelos) extract on ovarian weight and corpus luteum numberof the female white rat. The research design of posttest only control group design with animal tries Hundrednorvegicus female type, aged 8-10 months, weight 200-250g counted 24 tail divided 4 group. After the vaginalsmear is done in the same phase of the proestrus for 12 days, the animals try to be treated with Maja Leaf(Aegle Marmelos) extract. Rats in group 1 (K1) control group, in group 2 (K2) were given Maja Leaf (AegleMarmelos) extract dose 0,5g/kgBB, group 3 (K3) were given Maja Leaf (Aegle Marmelos) extract dose 1g/kgBB and group 4 (K4) were given Maja Leaf (Aegle Marmelos) extract dose of 1.5g/kgBB. At the end ofthe study all rats were taken ovaries for weight and number of corpus luteum. Analysis with Anova-oneway.Anovaone-way analysis results show p-value<0,05 so it can be concluded that there is a significant differencebetween K1 and K3. This research can be concluded Maja Leaf (Aegle Marmelos) extract effectively decreaseovarium weight and corpus luteum amount in female white rat. In Maja Leaf (Aegle Marmelos) extracts caninhibit follicular development through suppression of FSH levels resulting in reduced number of follicles andcorpus luteum ovaries. Many at least the corpus luteum is closely related to the amount of ovum being ovulated.